Using subsidies to enhance access to maternal and newborn health care in remote villages - Antonella Bancalari; Pedro Bernal; Maria Fernanda Garcia; Pablo Ibarrarán; Emmanuelle Monin; Paola Zuniga (Inter-American Development Bank (IDB), 2024)
This paper investigates the effects of alleviating remoteness constraints on access to quality maternal and newborn health care. Using a cluster-randomized controlled trial, we provided transportation vouchers to impoverished pregnant women residing in remote Nicaraguan villages located approximately five hours from the nearest health center, along with accommodations vouchers for maternal waiting homes. These vouchers were provided to the women and to companions of their choosing. The subsidies increased the utilization of quality antenatal care, institutional delivery, and quality postnatal care for mothers and newborns. Additionally, neonatal and infant mortality rates, as well as fertility rates, decreased in treated communities five years after the intervention began.
Keywords: 330; Mütter; Kinder; Ländliches Gesundheitswesen; Gutscheinsystem; Nicaragua